2017
DOI: 10.1080/21691401.2017.1374284
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of BACH1 inhibits invasion and migration of prostate cancer cells by altering metastasis-related gene expression

Abstract: BACH1 is overexpressed in prostate cancer. Because this promotes invasion and migration, it may facilitate metastasis of prostate cancer. Thus, BACH1 is a potential therapeutic target for metastatic prostate cancer. BACH1 silencing therapy can be considered as a novel and effective adjuvant in prostate cancer targeted therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…CXCR4: C-X-C chemokine receptor type 4; miR: microRNA; MMP9: matrix metalloproteinase-9; VEGFR: vascular endothelial growth factor receptor [Color figure can be viewed at wileyonlinelibrary.com] expression ( Figure 7). These results are consistent with our previous results which were reached by specific silencing of Bach-1 (Shajari et al, 2018). In line with our present results and previous results, we suggested that miR-142-3p might regulate the expression of CXCR4, MMP9, and VEGFR through silencing of Bach-1 mRNA.…”
Section: The Mir-142-3p Mimic Sequence Could Increase the Level Of supporting
confidence: 94%
“…CXCR4: C-X-C chemokine receptor type 4; miR: microRNA; MMP9: matrix metalloproteinase-9; VEGFR: vascular endothelial growth factor receptor [Color figure can be viewed at wileyonlinelibrary.com] expression ( Figure 7). These results are consistent with our previous results which were reached by specific silencing of Bach-1 (Shajari et al, 2018). In line with our present results and previous results, we suggested that miR-142-3p might regulate the expression of CXCR4, MMP9, and VEGFR through silencing of Bach-1 mRNA.…”
Section: The Mir-142-3p Mimic Sequence Could Increase the Level Of supporting
confidence: 94%
“…Accumulating data establish BACH1 as a critical facilitator of tumorigenesis and metastasis in breast (Lee et al, 2013), colon (Davudian et al, 2016b), prostate (Shajari et al, 2018) ovarian (Han et al, 2019), and lung (Lignitto et al, 2019;Wiel et al, 2019) cancer. Elevated levels of BACH1 expression have been linked to a higher risk of breast cancer recurrence in patients (Liang et al, 2012), whereas association with metastatic spread and poorer prognosis has recently been suggested in the case of human ovarian cancer (Han et al, 2019) and lung adenocarcinoma (Lignitto et al, 2019;Wiel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of Raf kinase inhibitory protein during tumor expansion results in higher expression of BACH1 and its target genes C-X-C chemokine receptor type 4 (CXCR-4) and matrix metal-loproteinase1 (MMP1), established drivers of tumor progression and metastasis (Foley & Kuliopulos, 2014;Mishan et al, 2016). Furthermore, ablation of BACH1 in human colon carcinoma (Davudian et al, 2016b) or in prostate cancer cells (Shajari et al, 2018) prevents cell growth, migration, and invasion in vitro, decreasing the expression of its main metastasisrelated genes, MMP1, let-7a, and CXCR4. Interestingly, cxcr4 is expressed in the somites and the endothelium of zebrafish embryos (Chong et al, 2001), where we detect the expression of both bach2a and bach2b transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the hypothesis that miR-135a is involved in CC progression, which may function as an oncogenic factor. BACH1, a member of the basic leucine zipper transcription factor family, is a critical participant in the regulation of oxidative stress [24] .Recent researches demonstrated that BACH1 is a widely expressed transcriptional repressor, which takes part in cell cycle progression, apoptosis, and the hypoxia response negatively through the targeted genes [25][26][27][28] .As one of them, heme-oxygenase-1 (HO-1) might be significant in induction of the tumorigenic pathway. The expression of HO-1 increases significantly in various types of cancer, which is proved to promote tumor growth and metastasis and suppress the apoptosis of tumor cells.…”
Section: Resultsmentioning
confidence: 99%